2017
DOI: 10.1039/c7ra05993k
|View full text |Cite
|
Sign up to set email alerts
|

Modular synthesis of thiazoline and thiazole derivatives by using a cascade protocol

Abstract: The first common synthetic protocol for thiazolines and thiazoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Intermediate 5-methyl-2-(pyridin-3-yl)-1,3-thiazole-4-carbohydrazide (1) was prepared as reported earlier [17,18] by the condensation of ethyl 5-methyl-2-(pyridin-3-yl)thiazole-4-carboxylate with hydrazine hydrate as outlined in Scheme 1. Furthermore, both 5-methyl-2-(pyridin-3-yl)-1,3thiazole-4-carbohydrazide (1) and 4-fluorobenzladehyde were taken in equal quantities and a catalytic amount of acetic acid was added and refluxed for 4 h. Following this, the synthesized compound was confirmed by elemental analysis, FT-IR, LCMS, 1 H-NMR, and 13 C-NMR.…”
Section: Resultsmentioning
confidence: 99%
“…Intermediate 5-methyl-2-(pyridin-3-yl)-1,3-thiazole-4-carbohydrazide (1) was prepared as reported earlier [17,18] by the condensation of ethyl 5-methyl-2-(pyridin-3-yl)thiazole-4-carboxylate with hydrazine hydrate as outlined in Scheme 1. Furthermore, both 5-methyl-2-(pyridin-3-yl)-1,3thiazole-4-carbohydrazide (1) and 4-fluorobenzladehyde were taken in equal quantities and a catalytic amount of acetic acid was added and refluxed for 4 h. Following this, the synthesized compound was confirmed by elemental analysis, FT-IR, LCMS, 1 H-NMR, and 13 C-NMR.…”
Section: Resultsmentioning
confidence: 99%
“…In our quest to synthesize bioactive molecules 3537 and to develop new domino reactions to synthesize heterocycles, 38,39 we planned the synthesis of thiazolino-androstanedione derivatives by using our recently reported methodology, the synthesis of thiazoline derivatives ( 2 ) by reacting thioamides with γ-bromoenones ( 1 ). 40 Reaction of 6β-bromoandrostenedione ( 3 ) with thiourea derivatives formed aminothiazoloandrostenone derivative ( 4 ) by an unexpected mechanism. 41 Surprisingly, reaction of thioamide derivative ( 5 ) with the electrophile ( 3 ) did not form the product in refluxing ethanol, as we expected from our previous report (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Several methods for the synthesis of thiazoles and their derivatives were developed by various catalysts, conditions, and strategies [12][13][14][15][16][17][18][19][20][21]. From these methods, we were interested in the synthesis of thiazoles by condensation of α-halo ketones with thioamides [22][23][24][25][26][27][28]. Beyzaei et al reported the one-pot synthesis of thiazol-2(3H)-imines through nucleophilic substitution of chloride in 3chloroacetylacetone with thiocyanate group followed by cyclo condensation with various hydrazine or hydrazide derivatives.…”
Section: Introductionmentioning
confidence: 99%